Amino acid formula induces microbiota dysbiosis and depressive-like behavior in mice - Ji Hu; Kaixin He; Yifei Yang; Chuan Huang; Yiping Dou; Hao Wang; Guorong Zhang; Jingyuan Wang; Chaoshi Niu; Guoqiang Bi; Lan Zhang; Shu Zhu (Cell Reports, 2024)
Summary: Amino acid formula (AAF) is increasingly consumed in infants with cow’s milk protein allergy; however, the long-term influences on health are less described. In this study, we established a mouse model by subjecting neonatal mice to an amino acid diet (AAD) to mimic the feeding regimen of infants on AAF. Surprisingly, AAD-fed mice exhibited dysbiotic microbiota and increased neuronal activity in both the intestine and brain, as well as gastrointestinal peristalsis disorders and depressive-like behavior. Furthermore, fecal microbiota transplantation from AAD-fed mice or AAF-fed infants to recipient mice led to elevated neuronal activations and exacerbated depressive-like behaviors compared to that from normal chow-fed mice or cow’s-milk-formula-fed infants, respectively. Our findings highlight the necessity to avoid the excessive use of AAF, which may influence the neuronal development and mental health of children.